Digitalization and Work Environment on Employee Performance: The Mediating Role of Motivation at PT Bank KB Bukopin Tbk Samarinda Branch - Fenty Fauziah; Eka Riyanti Yusuf; Wahyuni Wahyuni; Joko Sabtohadi; Ray Septianis Kartika (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Digital transformation has changed banking operations and employee roles. PT Bank KB Bukopin Tbk introduced the SHINE Project in 2023 as a digital transformation initiative through training and organizational restructuring to improve employee capabilities and performance. Objective: This study examines the influence of digital training and work environment on employee performance, with motivation as a mediating variable at PT Bank KB Bukopin Tbk Samarinda Branch. Methods: This explanatory quantitative study involved all 40 employees using a census sampling technique. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: Digitalization (β = 0.279, p = 0.018) and work environment (β = 0.750, p = 0.000) significantly influence motivation, while motivation significantly affects employee performance (β = 0.703, p = 0.010). Digitalization and work environment do not directly affect performance. Motivation fully mediates the relationship between work environment and performance (β = 0.527, p = 0.018), but does not significantly mediate the relationship between digitalization and performance (β = 0.196, p = 0.072). Conclusion: Employee performance during digital transformation is primarily enhanced through increased motivation supported by digital training and a positive work environment.